Tofacitinib Induced Psoriasiform Lesion in a Patient With Rheumatoid Arthritis - Kemal Erol,; Ragıp Ertaş, (Archives of Rheumatology, 2020)
Paradoxical psoriasis or psoriasiform lesion is an adverse effect, represented by the occurrence of a psoriasiform lesion or exacerbation of psoriasis caused by the drugs normally used for the management of psoriasis. In this article, we present the first case of a 45-year-old male patient with rheumatoid arthritis who developed psoriasiform lesions following treatment with tofacitinib, and highlight the possible pathogenetic mechanisms involved in such an occurrence.